Transpacific partnership agreement and future of internet policing of copyright infringement in Malaysia - Abdul Ghani Azmi, Ida Madieha; Ismail, Suzi Fadhilah; Daud, Mahyuddin (Universiti Putra Malaysia Press, 2017)
Internet Service Providers (ISPs) are the gate keepers of internet and free flow of information and expression. The ISPs can also play a strategic role in policing the Internet from copyright infringing materials. As gatekeepers, they can block access and force others to identify the origin of the materials making them the best organisation to take action on the internet materials. The abandoned Trans-Pacific Partnership Agreement (TPPA) between Malaysia, United States of America (US) and another 10 countries in Asia and Pacific Region contains obligations that mandates ISPs to expeditiously remove or disable access to alleged infringing material upon acquiring actual or even with constructive knowledge of the infringement. Although TPPA is theoretically dead after the withdrawal of the US, it is still pertinent to consider its provision as it is the first global standards on ISP liabilities though negotiated under a free trade agreement. This paper examines the obligations under Malaysian Copyright Act 1987 and compare them with TPPA provisions on ISPs. It concludes that unless there is latent defect with the Malaysian notice and take down procedure, there is no compelling urgency for Malaysia to revise her procedure.